Filantropi Islam Melalui Pengembangan Wakaf Produktif - Ahmad Zaenur Rosyid (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2014)
This article is oriented to analyze the problem of dynamic management from one of institution in Central Java, which manages waqf, Masjid Agung Semarang (MAS). Many waqf assets are unmanaged intensively handled by MAS which is still in the process to be produced. Some problems analyzed in this article are about the factors as a challenging in the process of empowering for philanthropy movement based on waqf in MAS. And the other problem is about the dynamic of distribution from waqf MAS. This article used socio-legal approach as a field research. The data analyzed by qualitative method. The findings of the research showed that conflict has happened among the functionaries of waqf in MAS especially after the process of ruslag for land of MAS, 119 ha changed to be 250 ha handled by Cipto as the leader of company. The conflict has been happened for long time and founded many interpretations between BKM and kyai in Kauman Semarang. Then there is no harmony in this empowering for waqf in MAS. The second answer that philanthropy movement in MAS is operated in many ways, either for POM, market shopping, or other business managed by nazir (functionaries of waqf).